Time-series forecasting - Chatfield, Chris (Chapman & Hall, 2012)
Forecasting is an important activity in economics, commerce, marketing and various branches of science. This book is concerned with forecasting methods based on the use of time-series analysis. It is primarily intended as a reference source for practitioners and researchers in forecasting, who could, for example, be statisticians, econometricians, operational researchers, management scientists or decision scientists. The book could also be used as a text for a graduate-level course in forecasting. Some application areas, such as meteorology, involve specialist methods which are not considered in this book. The specialist area of judgemental forecasting is also not covered. Rather we concentrate on time-series forecasting methods which are applicable more generally, but especially in economics, government, industry and commerce.